L’IMPACT DES MAMMITES SUR LES PERFORMANCES DE LA REPRODUCTION(V.L). - TIKOUR, Mohamed Salah (My University, 2020)
Our study was to determine the impact of mastitis on reproduction, as well as the various germs involved in the region of Fornaka and Ain Nouissy (Mostaganem). Infectious mastitis is a major problem in animal husbandry because it causes significant economic losses for the milk industry. Indeed, they always go hand in hand with a drop in milk production in the affected quarters of the udder. This decrease is most marked in the case of clinical mastitis. Subclinical mastitis or hidden breast infections reduce productivity by up to 40% (Schaeren, 2006). Thus it can be said that the fertility of dairy cows has deteriorated significantly over the past decades, both nationally and internationally. Reproductive disorders are among the most difficult to analyze and control, due to their multifactorial origin and the often long delay between causes and their effects.
Keywords: Infectious mastitis; clinical mastitis; subclinical mastitis; multifactoria.